InnoSTRE E-Forum on International Business and Education Collaboration - Voon, Boo Ho (UiTM Sarawak, 2021)
An online Forum Discussion was conducted on 26 November 2020 in conjunction with the InnoSTRE 2020 Special Edition conference. Forum Chair Prof. Dr. Voon Boo Ho underscored the many important processes and stakeholders in the education be integrated and the quality must be consistently The Research Methodology course (English and Chinese) of UiTM Cawangan Sarawak, which aimed at [trading and assisting postgraduates from China, was also shared through a 1-minute promotional video. The panelists were impressed with the internationalization competence, academic capability and human resource diversity of Ii 1 VI Sarawak and hoped for strategic collaborations. and continuously to strengthen and sustain the education value-chain. Strategic collaborations with local and international partners would most probably be instrumental for the mutual benefit of ail stakeholders for greater prosperity.